The role of physical activity on healthcare utilization in China - Xiao-Lin Lei; Ke Gao; Huan Wang; Wei Chen; Gen-Rui Chen; Xing Wen (BMC, 2023)
Abstract Background Evidence on the role of physical activity (PA) on healthcare utilization and expenditure is limited in China. We aimed to examine the association between the total physical activity (TPA) per week, healthcare service use and expenditure. Methods We extracted the data from China Health and Retirement Longitudinal Study (CHARLS) 2011, 2013, and 2015. Participants more than 50 years old who completed the follow-up for the three waves were enrolled. We converted the volume of vigorous physical activity (VPA) into an equivalent volume of moderate physical activity (MPA) and calculated the TPA per week for each participant. 12,927 of the 17,708 participants in CHARLS were included in our analysis. More than one-third of participants over 50 years old never participate in any moderate or intensity activity, and the median of self-reported moderate or intensity PA was about 525 (IQR 0-1680) MET-minutes per week in 2015. Results Compared to inactive subjects, the highest level of TPA was significantly related to the decreased risk number of inpatient visits (IRR: 0.58; 95% CI:0.50-0.67, p < 0.001), inpatient hospital days (IRR: 0.60; 95% CI: 0.42-0.84, p < 0.01), healthcare expenditure (IRR: 0.71; 95% CI: 0.65-0.79, p < 0.001) and catastrophic health expenditures (OR: 0.57; 95% CI: 0.45-0.72, p < 0.001) after adjusting for covariates. Conclusions Engaging in moderate-to-vigorous PA may drive a potential decrease in healthcare utilization, healthcare expenditure and household financial risk with a dose-response relationship in China, and some possible policy implications in public health may be considered to promote exercise in the middle-aged and elderly to reduce the medical burden on individuals and healthcare systems.